Designing a Global Trading System to Maximize Innovation. Issue 1 (February 2014) - Atkinson, Robert
Abstract 'Innovation mercantilism' is on the rise with the result: less global innovation. Policy makers should: create an Innovation Trade Agreement whereby tariffs on all innovation products are eliminated; make development aid contingent upon nations renouncing innovation mercantilist policies; empower multinational firms to fight back by providing antitrust exemptions for cooperation to resist forced technology transfer requirements; develop new multilateral own trade agreements with real measures to stop innovation mercantilism; and develop cooperative international agreements to better support innovation and R&D.